An Empirical Evaluation of Individual Knowledge and Perception apropos to GST implementation in Delhi NCR - Kathuria, CS Rachna; Saxena, Niti; Upreti, Bandita (International Journal of Psychosocial Rehabilitation, 2020)
The much awaited Goods and Services Tax (hereinafter referred to as GST) was made effective in India w.e.f 1st July 2017. It has been more than two years that individuals are living and working in the GST regime. It was predicted that this new system of Indirect Taxes, which is going to subsume a number of Central and State Level Indirect Taxes, is going to revolutionize the Indian Taxation System. During the early stage of its implementation, many financial issues viz inflation, increase in cost of living, economic stability, successful implementation of GST, were a cause of concern. Government had undertaken various initiatives to spread awareness about GST by educating the professionals & general public at large to improve their understanding on the need of GST in taxation system. During the initial stages of implementation, the public seemed to be confused about the concept and operational aspects of GST. The benefits were proclaimed to be too many and it was considered to be friendly to all. However the real achievement is still a question. Many questions and complaints were reported to the related authorities for perusal and necessary action. The system is running and is improving continually. The government aims to provide benefits to one and all. However, still the perception of an individual towards the structure of the system and awareness about the system among individuals is a question. After two years of its implementation, this study aims to study the perception of different individuals towards basic provisions of GST and whether government has taken initiatives to create awareness among individuals, with further scope of research available for the study with professionals and businessmen.